2010
DOI: 10.1002/jsfa.4162
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-enhanced mass transfer in Halal compared with non-Halal chicken

Abstract: Dye penetration is an indication of meat permeability and so can be used as an estimate of marinading of meat. Thus the use of high-power ultrasound has potential in poultry-processing methods, in particular that of Halal chicken marination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 9 publications
3
17
1
2
Order By: Relevance
“…The quantity of NaCl solution penetration in the beef enhanced when the ultrasonic intensity and treatment time increase. The similar conclusion was found in the previous research which reported that chicken pieces with ultrasound treatment increased the distance of dye penetration compared to the controls at 30 min (Leal‐Ramos, Alarcon‐Rojo, Mason, Paniwnyk, & Alarjah, ).…”
Section: Resultssupporting
confidence: 90%
“…The quantity of NaCl solution penetration in the beef enhanced when the ultrasonic intensity and treatment time increase. The similar conclusion was found in the previous research which reported that chicken pieces with ultrasound treatment increased the distance of dye penetration compared to the controls at 30 min (Leal‐Ramos, Alarcon‐Rojo, Mason, Paniwnyk, & Alarjah, ).…”
Section: Resultssupporting
confidence: 90%
“…Leal-Ramos et al [9] showed that US increased the quantity of dye inside chicken meat samples by 6 and 13% after 15 and 30 min, respectively. This effect was much more pronounced in halal meat, which showed a 60% increase in dye absorption during the same periods.…”
Section: Resultsmentioning
confidence: 99%
“…Acoustic waves applied to solid-liquid systems increase the rate of mass transfer [8][9][10] by physically breaking down tissues, which creates microchannels and produces changes in the concentration gradients and the diffusion coefficients [7,8]. Studies have reported improved distribution of solutes [11] and changes in water retention capacity, resulting in less water loss [10], while conserving food sensory properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the lipids were completely extracted when using HES, as the fat content of cobia liver is 48.14%. Ultrasound enhanced mass transfer has previously been demonstrated during the sonication of chicken breast cubes in dye solution, as evidenced through weight gain and methylene blue penetration . The increase in extraction yield by HES can be attributed to ultrasound increasing mass transfer and enhancing hexane penetration, allowing for better extraction of the complex lipids.…”
Section: Resultsmentioning
confidence: 90%